Virtual Union, the Seeds of Hatred, and the Fraternal Joining of Hands: Leibniz and Toleration - Mogens Laerke (Journal of Modern Philosophy)
In this paper, I am interested in the conception of toleration that can be gleaned from the political and theological texts of Gottfried Wilhelm Leibniz. I argue that Leibniz did not defend a notion of toleration comparable to a standard modern conception. The modern conception is very often traced back to a constellation of writers contemporary with Leibniz including Locke, Bayle, and Spinoza. It involves an inclusive embrace of diversity, religious and otherwise, and an affirmation of toleration as a fundamental value in and by itself, intrinsically linked to an equally fundamental imperative of freedom of expression allowing such diversity to flourish publicly. Leibniz, however, understood toleration as a political tool to be employed in order to facilitate the reunion of the Christian churches; he did not consider it a constitutive value, or a value in and by itself, but rather saw it as a means to an end; he did not establish any intrinsic link between toleration and freedom of expression but promoted moderate forms of censorship. Most importantly, however, while clearly seeing it as something positive, he also detected deep ambiguities in the concept from which we have much to learn in our own assessment of modern toleration.